Adapting RARE to assess barriers to service receipt among people out of care. - Conviser, Richard; Singer, Merrill; Pounds, Moses Belt (Journal of health care for the poor and underserved, 2007)
This paper describes the components of Rapid Assessment, Response and Evaluation (RARE), developed for HIV prevention planning; the adaptation of its methods to services planning; the venues in which the use of RARE was recommended for the present Care System Assessment Demonstration Project; constraints on what projects using RARE and the system assessment model may expect to accomplish; the focus of RARE questions for the project, concerning the characteristics of PLWH not in regular primary care, the care system as PLWH not in care perceive and experience it, and characteristics of the physical and social environments in which they live; how information from RARE can contribute to the enhancement of care systems; and the types of questions that sites could ask to gather RARE information for services planning.
Keywords: Community Health Planning; Delivery of Health Care; Health Policy; Health Services Accessibility; HIV Infections; Humans; Medically Underserved Area; Needs Assessment; Primary Health Care; Program Development; Social Environment; United States